Laminin-Mediated Interactions in Thymocyte Migration and Development - Savino, Wilson; Mendes-da-Cruz, Daniella Arêas; Golbert, Daiane Cristina Ferreira; Riederer, Ingo; Cotta-de-Almeida, Vinicius (Frontiers in Immunology, 2015)
Intrathymic T cell differentiation is a key process for the development and maintenance of cell-mediated immunity, and occurs concomitantly to highly regulated migratory events. We have proposed a multivectorial model for describing intrathymic thymocyte migration. One of the individual vectors comprises interactions mediated by laminins, a heterotrimeric protein family of the extracellular matrix. Several laminins are expressed in the thymus, being produced by microenvironmental cells, particularly thymic epithelial cells. Also, thymocytes and epithelial cells express integrin-type laminin receptors. Functionally, it has been reported that the dy/dy mutant mouse (lacking the laminin isoform 211) exhibits defective thymocyte differentiation. Several data show haptotactic effects of laminins upon thymocytes, as well as their adhesion on thymic epithelial cells; both effects being prevented by anti-laminin or anti-laminin receptor antibodies. Interestingly, laminin synergizes with chemokines to enhance thymocyte migration, whereas classe-3 semaphorins and B ephrins, which exhibit chemorepulsive effects in the thymus, downregulate laminin-mediated migratory responses of thymocytes. More recently, we showed that knocking down the ITGA6 gene (which encodes the α6 integrin chain of laminin receptors) in human thymic epithelial cells, modulates a large number of cell-migration related genes, and results in changes of adhesion pattern of thymocytes onto the thymic epithelium. Overall, laminin-mediated interactions can be placed at the cross-road of the multivectorial process of thymocyte migration, with a direct influence per se, as well as by modulating other molecular interactions associated with the intrathymic trafficking events.